Hypertension-Causing Mutation in Peroxisome Proliferator–Activated Receptor γ Impairs Nuclear Export of Nuclear Factor-κB p65 in Vascular Smooth Muscle. Issue 1 (July 2017) - Mukohda, Masashi; Lu, Ko-Ting; Guo, Deng-Fu; Wu, Jing; Keen, Henry L.; Liu, Xuebo; Ketsawatsomkron, Pimonrat; Stump, Madeliene; Rahmouni, Kamal; Quelle, Frederick W.; Sigmund, Curt D.
Abstract : Selective expression of dominant negative (DN) peroxisome proliferator–activated receptor γ (PPARγ) in vascular smooth muscle cells (SMC) results in hypertension, atherosclerosis, and increased nuclear factor-κB (NF-κB) target gene expression. Mesenteric SMC were cultured from mice designed to conditionally express wild-type (WT) or DN-PPARγ in response to Cre recombinase to determine how SMC PPARγ regulates expression of NF-κB target inflammatory genes. SMC-specific overexpression of WT-PPARγ or agonist-induced activation of endogenous PPARγ blunted tumor necrosis factor α (TNF-α)–induced NF-κB target gene expression and activity of an NF-κB–responsive promoter. TNF-α–induced gene expression responses were enhanced by DN-PPARγ in SMC. Although expression of NF-κB p65 was unchanged, nuclear export of p65 was accelerated by WT-PPARγ and prevented by DN-PPARγ in SMC. Leptomycin B, a nuclear export inhibitor, blocked p65 nuclear export and inhibited the anti-inflammatory action of PPARγ. Consistent with a role in facilitating p65 nuclear export, WT-PPARγ coimmunoprecipitated with p65, and WT-PPARγ was also exported from the nucleus after TNF-α treatment. Conversely, DN-PPARγ does not bind to p65 and was retained in the nucleus after TNF-α treatment. Transgenic mice expressing WT-PPARγ or DN-PPARγ specifically in SMC (S-WT or S-DN) were bred with mice expressing luciferase controlled by an NF-κB–responsive promoter to assess effects on NF-κB activity in whole tissue. TNF-α–induced NF-κB activity was decreased in aorta and carotid artery from S-WT but was increased in vessels from S-DN mice. We conclude that SMC PPARγ blunts expression of proinflammatory genes by inhibition of NF-κB activity through a mechanism promoting nuclear export of p65, which is abolished by DN mutation in PPARγ. Abstract : Supplemental Digital Content is available in the text.